THE EFFECT OF THE DELOCALISATION THEORY IN THE CONTEXT OF ART. V (1) (E) OF THE NEW YORK CONVENTION – AN INVESTIGATIN OF UNIFORMITY IN ENFORCEMENT OF AWARDS IN VARIOUS JURISDICTIONS: DELOCALISATION IN PRACTICE (Journal of actual problems of jurisprudence, 2018)
The article depicts the advantages and disadvantages of delocalisation theory. And it is given real examples and cases from practice. In providing a fair response to the debatable questions discussed in the entire work, we can undoubtedly not only say that the delocalisation theory is needed not only as an absolute doctrine but also investigate as a qualified doctrine, support and encourage this idea henceforward. Notwithstanding, it is still contentious whether to treat the delocalisation of arbitration as the breakwater in retaining uniformity of awards in the landscape of international commercial arbitration, the trend towards delocalisation theory is shedding new light on issues that were debated vigorously in the last five decades. In any case, application of delocalisation theory has its own strengths and weaknesses as well as other modern doctrines.Key words: delocalization, arbitration, New York Convention, arbitration award, entry into force, jurisdiction, case, enforcement.